Evolution of the quality and dissemination of a Spanish scientific journal of Psychology: Anales de Psicología, 25 volumes published per year (1984-2009) - Romero Medina, Agustín (Anales de Psicología / Annals of Psychology, 2009)
The celebration of the 25 annual volumes of the Anales de Psi-cología journal in 2009 serves as a pretext to review the history of this jour-nal and its evolution in terms of: aims and editorial policy, organizational structure, format and layout, content selection, dissemination and impact. All this in the context of scientific journals of psychology in Spain and the growing trend by journal editors and advisory boards, documentation centers, and institutions and agencies (national and regional) for research assessment, to improve the criteria for evaluating the quality of journals and increasingly closer to international standards. Anales de Psicología jour-nal is in that way, as demonstrated in all of publishing quality data ana-lyzed in this work.